A cohort study assessing the sustainable long-term effectiveness of a childhood-obesity intervention in China. (25th July 2018) - Cao, Zhijuan; Hua, Jing; Zhang, Donglan; Thapa, Janani R; Wang, Shumei
Abstract: Background: Obesity has become a global epidemic, with substantial impacts on children's health. Numerous intervention studies for the prevention of obesity in children have been conducted during the most recent decade, but very few have evaluated the long-term and sustainable effectiveness of such prevention efforts. Methods: We conducted a follow-up study during September 2015 and September 2017, based upon a previous 3-year cluster randomized–controlled study (RCT) for a comprehensive childhood-obesity intervention in 14 primary schools in Shanghai, China. A total of 929 students were enrolled in the study. Generalized estimating equation approaches were applied to analyse student's body mass index (BMI), BMI z-score at baseline and three annual long-term follow-ups. Results: Three years after the end of the RCT study, the odds of developing obesity and the odds of developing obesity or overweight in the intervention group were both lower than in the control group among girls [OR(obesity)   =   0.299, p  =   0.010 and OR (overweight/obesity) =   0.493, p  =   0.013]; the odds of developing obesity or overweight in the intervention group was lower than in the control group among boys (OR = 0.369, p  =   0.017). Compared with the baseline, the BMI z-scores in the intervention group were lower than those in the control group for both normal-weight students (–0.027) and overweight or obese students (–0.074). Conclusions: The 3-year RCT showed significant and reliable long-term effects on preventing childhood obesity, particularly among girls.